Epitope Prediction Assays Combined with Validation Assays Strongly Narrows down Putative Cytotoxic T Lymphocyte Epitopes - Peng Peng Ip; Hans W. Nijman; Toos Daemen (Vaccines, 2015)
Tumor vaccine design requires prediction and validation of immunogenic MHC class I epitopes expressed by target cells as well as MHC class II epitopes expressed by antigen-presenting cells essential for the induction of optimal immune responses. Epitope prediction methods are based on different algorithms and are instrumental for a first screening of possible epitopes. However, their results do not reflect a one-to-one correlation with experimental data. We combined several in silico prediction methods to unravel the most promising C57BL/6 mouse-restricted Hepatitis C virus (HCV) MHC class I epitopes and validated these epitopes in vitro and in vivo. Cytotoxic T lymphocyte (CTL) epitopes within the HCV non-structural proteins were identified, and proteasomal cleavage sites and helper T cell (Th) epitopes at close proximity to these CTL epitopes were analyzed using multiple prediction algorithms. This combined in silico analysis enhances the precision of identification of functional HCV-specific CTL epitopes. This approach will be applicable to the design of human vaccines not only for HCV, but also for other antigens in which T-cell responses play a crucial role.